The Self-Reflective Writing Scale (SRWS): a new measure to assess self-reflection following self-experiential cognitive behaviour therapy training. Issue 4 (4th July 2018) - So, Suzanne Ho-wai; Bennett-Levy, James; Perry, Helen; Wood, Debbie Helen; Wong, Chee-wing
ABSTRACT: It has been hypothesized that capacity for reflection is a key metacognitive skill in therapist development. However, the measurement of reflection in psychotherapy has proved problematic. The primary purpose of the present study has been to develop a theory-based measure of reflection, the Self-Reflective Writing Scale (SRWS). The SRWS encompasses measures of personal-self reflection (PS) and therapist-self reflection (TS). The development of the SRWS is described. Reliability and validity of the SRWS were assessed in the context of a self-practice/self-reflection (SP/SR)cognitive behavioural therapy training program where clinical psychology students practiced therapy techniques on themselves and reflected on the experience. Trainers' co-ratings of the SRWS reached an acceptable level of inter-rater reliability. As a test of criterion-related validity, the association between students' reflective skill and an independent rating of their interpersonal skills was examined. As predicted, the level of therapist-self reflectivity was positively correlated with interpersonal skills in the therapeutic context. However, personal-self reflectivity was negatively correlated with students' interpersonal skills. We suggest a possible explanation for this apparently surprising result. Although these tests of reliability and validity are preliminary and the results are modest, it is suggested that the SRWS holds promise as a measure of therapists' reflective ability.